RELEVANSI HUKUM PEMBENTUKAN PERMA NO 1 TAHUN 2019 TENTANG PERSIDANGAN SECARA ELEKTRONIK YANG MENGGANTI PASAL 230 KUHAP TENTANG PERSIDANGAN SECARA LANGSUNG - Charin, Ilham Putra; HZ, Evi Deliana; Junaidi, Junaidi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2024)
This research analyzes the legal relevance of the formation of Supreme CourtRegulation (PERMA) Number 1 of 2019 concerning Case Administration and TrialElectronically in Court. Prior to the creation of PERMA No. 1 of 2019, traditional courtproceedings (in-person hearings) were conducted, as explained in the Indonesian Code ofCriminal Procedure (KUHAP) Article 230 paragraph 1, which states: “Court hearingsare conducted in the courthouse in the courtroom.” The theoretical framework used toanalyze the issues in this research are theory of legislative regulation formation and thelegal hierarchy theory introduced by Hans Kelsen, which posits that the legal system is ahierarchical ladder with layered norms. Norms determined by higher legal norms providethe validity basis for the entire legal framework that constitutes a unity.Using a normative juridical research method, the findings of this research indicate thatthe establishment of PERMA No. 1 of 2019 is not in conflict with the provisions ofArticle 230 of the Indonesian Code of Criminal Procedure. This regulation does notviolate the principle of the hierarchy of legislation in Indonesia, considering that PERMAis subordinate to laws with higher authority. Therefore, PERMA is consistent with theprinciple of lex superiori derogat legi inferiori, which stipulates that lower regulationsmust not contradict higher regulations. The authority of the Supreme Court to enactPERMA is a derivative (delegated) authority. Delegation of legislative authority to theSupreme Court is carried out with the intention of filling legal gaps that cannot always beaddressed by legislation. PERMA Number 1 of 2019 serves as a legal gap filler becauseprovisions of general and abstract laws still need to be detailed through lower-levelregulations that are concrete and technical.Keywords: relevance, hierarchy, Supreme Court regulation, Indonesian Code ofCriminal Procedure, trial.